Anti acne Solid Soap Antimicrobial Activity Test against Staphylococcus aureus Bacteria that Causes Acne - Ade Indra Utama; Mades Fifendy; Linda Advinda (Jurnal Serambi Biologi, 2022)
The purpose of this study was to determine the antimicrobial activity of the anti-acne solid soap type and the effect of its concentration as well as the interaction between the anti-acne solid soap type and its concentration against Staphylococcus aureus bacteria that causes acne. This research was conducted from October - December 2021 at the Microbiology Laboratory, Faculty of Mathematics and Science, Universitas Negeri Padang. The methodology used in this study was an experiment with disc diffusion method using a completely randomized design (CRD) in a factorial consisting of 6 treatments and 3 repetitions with anti acne solid soap at concentrations of 2.5%, 5%, 7.5%, 10 %, 12.5% (w/v) and control (sterile distilled water). The inhibition zone diameter data were statistically analyzed using ANOVA, with = 5% and continued with Duncan's New Multiple Range Test (DNMRT) further test. The results of this study showed that both anti-acne solid soaps were able to provide antimicrobial activity against S. aureus bacteria at different concentrations because brand A and J solid anti-acne soap were able to form the highest average diameter of inhibition zones of 2.67 cm and 4, respectively. ,39 cm at 5% concentration. From the statistical analysis data using ANOVA, it was seen that the type and concentration of anti-acne solid soap had no significant effect on S. aureus bacteria and there was no interaction between the type of anti-acne solid soap and its concentration on S. aureus bacteria that causes acne.